Increasing the effectiveness of recovering, identifying and separating spermatozoa on post-coital vaginal swabs taken in sexual assault cases. Issue 1 (December 2019) - Kennedy, Finlay; Thomson, Jim; Clayton, Tim
Abstract: In 2016, EFS began a continuous improvement project designed to increase success rates in sexual assault cases targeting, in particular, intimate swabs where low numbers of spermatozoa were present. The objectives of the project were (1) to optimise the recovery of semen from cotton-based vaginal swabs, (2) to increase the effectiveness of searching microscope slides to identify sparsely distributed spermatozoa and (3) to reduce the incidence of carryover female DNA in the seminal fraction after differential lysis. Since implementation, this modified protocol, which we have called 'SpermTrap®', has improved laboratory success rates markedly.